Real-World Adherence and Discontinuation of Glucagon-Like Peptide-1 Receptor Agonists Therapy in Type 2 Diabetes Mellitus Patients in the United States - Weiss T; Carr RD; Pal S; Yang L; Sawhney B; Boggs R; Rajpathak S; Iglay K (Patient Preference and Adherence, 2020)
Tracey Weiss,1 Richard D Carr,2,3 Sampriti Pal,4 Lingfeng Yang,1 Baanie Sawhney,4 Robert Boggs,1 Swapnil Rajpathak,1 Kristy Iglay1 1Center for Observational and Real-World Evidence, Merck & Co., Inc, Kenilworth, NJ, 07033, USA; 2Global Medical Affairs, Merck Sharp & Dohme Limited (MSD), Hoddesdon, EN11 9BU, UK; 3Hatter Cardiovascular Institute, University College London, London, WC1E 6HX, UK; 4Real-World Evidence, Complete HEOR Solutions (CHEORS), Pennsylvania, PA, 19454, USACorrespondence: Tracey Weiss Tel +1 (908) 873-9697Email tracey.weiss@merck.comAim: To assess adherence and discontinuation of injectable glucagon-like peptide-1 receptor agonists (GLP-1 RA) at 12 and 24 months among adult type 2 diabetes mellitus (T2DM) patients in the United States initiating GLP-1 RA using the administrative claims-based database, Optum Clinformatics® Data Mart 7.1.Methods: A retrospective study was conducted from 01/2009 to 12/2017. Patients were required to be continuously enrolled for 12 months prior to their first GLP-1 RA prescription. Proportion of days covered (PDC) from prescription claims ≥ 0.80 defined adherence. Discontinuation was defined as a ≥ 90-day gap from the last date of GLP-1 RA supply to the first date of subsequent prescription claim.Results: A total of 4791 T2DM patients had ≥ 1 and 3907 had ≥ 2 GLP-1 RA prescription claims. 50.9% and 47.4% of patients were adherent at 12 and 24 months, respectively. Adherence was significantly higher among patients on weekly vs daily doses (p< 0.001). Median time to discontinuation was 13 months. The discontinuation rate was 47.7% and 70.1% at 12 and 24 months, respectively, with differences at 24 months for age and dosing frequency (p< 0.001 for both).Conclusion: Over half of T2DM patients initiating GLP-1 RA were non-adherent and the majority (70.1%) discontinued therapy by 24 months. Reasons for non-adherence and discontinuation merit further research.Keywords: GLP-1 RA, adherence, discontinuation, United States